Withstanding Vulnerability Throughout Adult Life 2023
DOI: 10.1007/978-981-19-4567-0_15
|View full text |Cite
|
Sign up to set email alerts
|

Ageing and Reserves

Abstract: In this chapter we elaborate on our conceptual view on vulnerability being the result of insufficient reserve build-up across the life course in various domains (e.g., cognitive reserve and relational reserve). Specifically, we propose that certain individuals are more vulnerable (than other, less vulnerable individuals) to impairments in human functioning because of insufficient reserves accumulated over their life course, which consequently exposes those individuals to greater difficulty to deal with threate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Our findings, which indicate a stronger positive association between inadequate health literacy and the number of prevalent unhealthy lifestyle behaviours among socially isolated respondents, are consistent with the theory that health outcomes, health-related behaviours, and health literacy should be placed in the context of the personal and socio-physical environments of individuals [ 47 ]. Building on the theory of social capital introduced by Bourdieu in the 80s [ 48 ], recent conceptual frameworks have notably focused on the importance of “social reserve,” referring to the accumulated social resources that individuals possess, which can act as a buffer during times of adversity or stress, promoting better health outcomes in older age [ 49 , 50 ]. Studies focusing specifically on the interplay between social context and health literacy have suggested that health literacy functions more as a social practice than simply an individual competence [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings, which indicate a stronger positive association between inadequate health literacy and the number of prevalent unhealthy lifestyle behaviours among socially isolated respondents, are consistent with the theory that health outcomes, health-related behaviours, and health literacy should be placed in the context of the personal and socio-physical environments of individuals [ 47 ]. Building on the theory of social capital introduced by Bourdieu in the 80s [ 48 ], recent conceptual frameworks have notably focused on the importance of “social reserve,” referring to the accumulated social resources that individuals possess, which can act as a buffer during times of adversity or stress, promoting better health outcomes in older age [ 49 , 50 ]. Studies focusing specifically on the interplay between social context and health literacy have suggested that health literacy functions more as a social practice than simply an individual competence [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Building on the theory of social capital introduced by Bourdieu in the 80s [48], recent conceptual frameworks have notably focused on the importance of "social reserve," referring to the accumulated social resources that individuals possess, which can act as a buffer during times of adversity or stress, promoting better health outcomes in older age [49,50]. Studies focusing specifically on the interplay between social context and health literacy have suggested that health literacy functions more as a social practice than simply an individual competence [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…People who manage to maintain a certain level of functional fitness gain some protection concerning various health conditions (e.g., heart disease, diabetes, obesity, cancers), as well as being able to guarantee the execution of activities of daily living in an independent and safe [11][12][13]. Additionally, benefits at the psychological level are also evident, especially concerning emotional well-being, increased cognitive function, and a high perception of quality of life [14].…”
Section: Physical Activity and Functional Fitness Relationshipsmentioning
confidence: 99%